Dolomite and phosphogypsum surface application effects on annual crops nutrition and yield - Soratto, Rogério Peres [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (Amer Soc Agronomy, 2008)
Brazil has extensive area with acid soils. Using phosphogypsum and soil acidity tolerant cultivars are alternatives to crop establishment in no-till system without previous limestone incorporation in many agricultural soils of Brazil. However, it remains unknown how phosphogypsum and limestone surface application affects rice (Oryza sativa L.) and common bean (Phaseolus vulgaris L.) nutrition and yield under a no-till system. A field experiment was conducted in a sandy clay loam, kaolinitic, thermic Typic Haplorthox, previously cultivated under conventional tillage, in Botucatu, Sao, Paulo State, Brazil. Treatments included four dolomitic limestone rates (0, 1100, 2700, and 4300 kg ha(-1)), two phosphogypsum rates (0 and 2100 kg ha(-1)), and two upland rice cultivars (Caiapo and IAC 202). in 2002-2003, and two bean cultivars (Perola and Carioca), in 2003-2004. Both amendments were applied on the surface, without soil incorporation. The content of Ca, Mg, and Mn in flag leaves and rice yield increased with limestone surface application. Liming increased the shoot dry matter of IAC 202 rice. Phosphogypsum increased S contents in leaves of both rice cultivars, and resulted in higher grain yield in the Caiapo rice. Liming increased K contents in leaves of both bean cultivars. In the absence of phosphogypsum, liming increased S contents and grain yield of bean. Content of Mg in leaves was reduced by phosphogypsum in lower limestone rates. In phosphogypsum presence, liming reduced Zn contents in leaves and increased bean shoot dry matter. Phosphogypsum increased Ca and S, and reduced Mg contents in bean leaves. Using soil acidity tolerant cultivars promoted higher crop yields in no-till systems establishment, even when the effective soil amelioration had not yet been achieved.